Suicide epidemics: the impact of newly emerging methods on overall suicide rates - a time trends study - Chang Shu-Sen; Thomas Kyla; Gunnell David (BMC Public Health, 2011)
Abstract Background The impact of newly emerging, popular suicide methods on overall rates of suicide has not previously been investigated systematically. Understanding these effects may have important implications for public health surveillance. We examine the emergence of three novel methods of suicide by gassing in the 20th and 21st centuries and determine the impact of emerging methods on overall suicide rates. Methods We studied the epidemic rises in domestic coal gas (1919-1935, England and Wales), motor vehicle exhaust gas (1975-1992, England and Wales) and barbecue charcoal gas (1999-2006, Taiwan) suicide using Poisson and joinpoint regression models. Joinpoint regression uses contiguous linear segments and join points (points at which trends change) to describe trends in incidence. Results Epidemic increases in the use of new methods of suicide were generally associated with rises in overall suicide rates of between 23% and 71%. The recent epidemic of barbecue charcoal suicides in Taiwan was associated with the largest rise in overall rates (40-50% annual rise), whereas the smallest rise was seen for car exhaust gassing in England and Wales (7% annual rise). Joinpoint analyses were only feasible for car exhaust and charcoal burning suicides; these suggested an impact of the emergence of car exhaust suicides on overall suicide rates in both sexes in England and Wales. However there was no statistical evidence of a change in the already increasing overall suicide trends when charcoal burning suicides emerged in Taiwan, possibly due to the concurrent economic recession. Conclusions Rapid rises in the use of new sources of gas for suicide were generally associated with increases in overall suicide rates. Suicide prevention strategies should include strengthening local and national surveillance for early detection of novel suicide methods and implementation of effective media guidelines and other appropriate interventions to limit the spread of new methods.